'Unlocking' Pelan Pembangunan Pendidikan Malaysia 2015-2025 (Pendidikan Tinggi) - Ismail, Asma (2016)
MALAYSIA EDUCATION BLUEPRINT 2015-2025 (HIGHER EDUCATION) - Addressing Current & Future Challenges in Malaysian Higher Education